«ALWAYS FELT TEACHER...» - Baran, Ye. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Leonid Roudnitkyi. World code of the Ukrainian writing: chosen study articles of literature and researches /Avt. peredm. L.Roudnitsky; Avt. pislyamovi D. Pavlychko;, author St.Хороб; Author of prim. N.Vivcharic. - Ivano-Frankivs’k: Vid-vo Pricarpatscogo national university of the name of Vasil Stefanik, 2010. - 334 p.